Digital Gap caused by Demographic Condition among Rural Society - Oktavianoor, Renaldy (Universitas Airlangga, 2020)
AbstractDigital gap or digital divide is a problem that emerged in the community because of the development of ICT (information and communication technology) are less prevalent. This problem is often experienced by rural communities, for urban communities first get a chance to feel the impact of the development of ICT infrastructure when compared with rural communities. Ariyanti stated that the digital divide is caused by four factors, infrastructure, skill, language content, and utilization. Therefore, researchers interested in conducting research in Argosari village, Lumajang. This research uses descriptive quantitative method with a sampling technique using accidental sampling. The results of this research found that all respondents own a smartphone, but internet access availability in the village Argosari still poor. Skill owned by villagers of Argosari still much in the learning phase using ICT tools, with a percentage of 64%. The ability of the respondents in understanding the English language content still many expressed very difficult in understanding the English language content on the Internet, with a percentage of 51%. On the utilization of ICT tools, 80% of respondents have started using their ICT tools for browsing activity. Researchers found that there is a relationship between the age of a person with activities you do while using technological devices; there is a relationship between a person's last education level with their skills in operating the technological features of the device; there is a relationship between education level last person with their skill in operating a search engine; there is a relationship between a person's last level of education with their ability to understand content in English.Keywords: digital divide; rural communities; information and communication technology AbstrakKesenjangan digital atau digital divide merupakan sebuah permasalahan yang muncul di masyarakat karena adanya perkembangan TIK (teknologi informasi dan komunikasi) yang kurang merata. Permasalahan ini kerap dialami oleh masyarakat rural (masyarakat pedesaan), karena masyarakat urban (masyarakat perkotaan) lebih dulu mendapatkan kesempatan untuk merasakan dampak pembangunan infrastruktur TIK jika dibandingan dengan masyarakat rural. Ariyanti menyatakan bahwa kesenjangan digital disebabkan oleh 4 faktor, yaitu faktor infrastruktur, skill, konten bahasa, dan pemanfaatan. Karena itu peneliti tertarik untuk melakukan penelitian di Desa Argosari, Lumajang. Penelitian ini menggunakan metode penelitian kuantitatif deskriptif dengan teknik pengambilan sampel menggunakan accidental sampling. Hasil dari penelitian ini ditemukan bahwa seluruh responden sudah memiliki smartphone, akan tetapi akses internet yang tersedia di Desa Argosari masih buruk. Skill yang dimiliki masyarakat Desa Argosari masih banyak yang dalam tahap belajar menggunakan perangkat TIK, dengan persentase 64%. Kemampuan para responden dalam memahami konten yang berbahasa inggris masih banyak yang menyatakan sangat kesusahan dalam memahami konten yang berbahasa Inggris di internet, dengan persentase 51%. Pada bagian pemanfaatan perangkat TIK, sebanyak 80% responden sudah mulai menggunakan perangkat TIK mereka untuk aktivitas browsing. Peneliti menemukan bahwa terdapat hubungan antara usia seseorang dengan aktivitas yang dilakukan saat menggunakan perangkat teknologi; terdapat hubungan antara jenjang pendidikan terakhir seseorang dengan skill mereka dalam mengoperasikan fitur pada perangkat teknologinya; terdapat hubungan antara jenjang pendidikan terakhir seseorang dengan skill mereka dalam mengoperasikan search engine; terdapat hubungan antara jenjang pendidikan terakhir seseorang dengan kemampuan mereka dalam memahami konten yang berbahasa Inggris.Kata kunci: kesenjangan digital; masyarakat rural; teknologi informasi dan komunikasi